2021
DOI: 10.3390/biomedicines9091216
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcoholism and HHV-6 Infection Synergistically Promote Neuroinflammatory Microglial Phenotypes in the Substantia Nigra of the Adult Human Brain

Abstract: Both chronic alcoholism and human herpesvirus-6 (HHV-6) infection have been identified as promoters of neuroinflammation and known to cause movement-related disorders. Substantia Nigra (SN), the dopaminergic neuron-rich region of the basal ganglia, is involved in regulating motor function and the reward system. Hence, we hypothesize the presence of possible synergism between alcoholism and HHV-6 infection in the SN region and report a comprehensive quantification and characterization of microglial functions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Although the underlying mechanism is still unknown, based on the history of viral inflammatory diseases, it is expected that dysregulation of the adaptive immune response [157,158] could be one critical component of disease progression. Activation of CD4 + Th1 cells upon SARS-CoV2 infection and subsequent production of anti-viral cytokine IFN-γ might be beneficial (25) for initial virus killing; however, prolonged activation of these T cells might result in the development of a pathological inflammatory response (Fig. 5) including an elevated production of chemokines and cytokines released activated macrophages and microglia.…”
Section: Long-haul Covid and Chronic Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Although the underlying mechanism is still unknown, based on the history of viral inflammatory diseases, it is expected that dysregulation of the adaptive immune response [157,158] could be one critical component of disease progression. Activation of CD4 + Th1 cells upon SARS-CoV2 infection and subsequent production of anti-viral cytokine IFN-γ might be beneficial (25) for initial virus killing; however, prolonged activation of these T cells might result in the development of a pathological inflammatory response (Fig. 5) including an elevated production of chemokines and cytokines released activated macrophages and microglia.…”
Section: Long-haul Covid and Chronic Fatiguementioning
confidence: 99%
“…One potential mechanism could be the escape of persistently infected CD4 + T cells from the above-mentioned acute apoptotic pathway that potentially stimulate an inflammatory response in macrophages and glial cells. A recent report also suggests that HHV6A directly stimulates the inflammation and migration of microglial cells via activation of TREM2 and ApoE [ 24 ].Therefore, active HHV6 infection, but not an acute immunosuppressive event, may be directly responsible for responsible for the microglial activation [ 25 ], and possible demyelination [ 26 ]. Furthermore, a recent study [ 27 ] identified that patients with demyelination in CNS displayed HHV6-immunoreactive oligoclonal bands in their cerebrospinal fluid indicating a potential link between multiple sclerosis (MS)-like encephalopathy and HHV6-infection.…”
Section: Introductionmentioning
confidence: 99%
“…The high HHV-6 DNA load in patients with ciHHV-6 can sometimes lead to misdiagnosis due to the assumption of active HHV-6 infection but in this patient the clinical picture was consistent with HHV-6 infection with improvement on appropriate treatment. While elevated HHV-6 levels can be seen in settings such as alcoholism and use of immunosuppressives, clinical correlation is needed to establish a cause and effect relationship while looking for other possible etiologies for patient’s symptoms [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Both chronic alcoholism and human herpesvirus-6 (HHV-6) infection may cause movement-related disorders and promote neuroinflammation. Jain et al [19] observed decreased perivascular CD68 + /Iba1 + microglia in the postmortem brain from alcoholic individuals as compared to the dominant CD68 + /Iba1 − microglial subpopulation in the control brains. All the control brains were HHV-6 negative.…”
mentioning
confidence: 97%